Effectiveness of Cognitive Training for School-Aged Children and Adolescents With Attention Deficit/Hyperactivity Disorder: A Systematic Review - Veloso, Andreia; Vicente, Selene G.; Filipe, Marisa G. (Frontiers in Psychology, 2020)
Problems with executive functions (EF) are hallmark characteristics of Attention Deficit/Hyperactivity Disorder (ADHD). Therefore, this review analyzed the efficacy of cognitive training for EF in reducing ADHD symptomatology and improving educational, interpersonal, and occupational outcomes in children and adolescents with this disorder. A systematic search was carried out. From 2008 to 2018, the following databases were searched: Academic Search Complete, ERIC, MEDLINE with Full Text, PsycARTICLES, PsycINFO and Psychology, and Behavioral Sciences Collection. Twenty-six studies were included in this review. Of the 21 studies that reported performance-based measures of EF, 16 found improvements and five did not. Overall, twenty-one studies showed positive transfer effects on ADHD symptomatology, academic improvement, reduced off-task behavior, and/or enhanced social skills. Of the 11 studies that performed follow-up sessions, nine concluded that the treatment effects were maintained over time. In sum, results showed that cognitive training can be an effective intervention for children and adolescents with ADHD and might be a complementary treatment option for this disorder.